2011
DOI: 10.4236/jmmce.2011.1015111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steel Fibers and Iron Filings on Thermal and Mechanical Properties of Concrete for Energy Storage Application

Abstract: An experimental study on the thermal properties of iron filings and steel-fiber-reinforced concrete for solar/thermal energy storage application is presented in this report. It takes into account the results of measurements of thermal conductivity, thermal resistivity, thermal diffusivity and the results of compressive strength, density as well as energy storage capacity calculated from the knowledge of the above measured parameters. The experimental testing method is described as well: based upon the linear h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
3
8
0
1
Order By: Relevance
“…The rough surface of the RIP may provide the formation of a stronger interfacial transition zone (ITZ) between the cement paste and the aggregate, which is a crucial factor for improving the strength of cement-based composites [32,33]. The findings are in good agreement with the literature [12][13][14][15][16][17][18][19][20]. This study reveals that the optimum replacement content of NS by RIP is 30% due to its significantly higher compressive strength.…”
Section: Compressive Strengthsupporting
confidence: 86%
See 1 more Smart Citation
“…The rough surface of the RIP may provide the formation of a stronger interfacial transition zone (ITZ) between the cement paste and the aggregate, which is a crucial factor for improving the strength of cement-based composites [32,33]. The findings are in good agreement with the literature [12][13][14][15][16][17][18][19][20]. This study reveals that the optimum replacement content of NS by RIP is 30% due to its significantly higher compressive strength.…”
Section: Compressive Strengthsupporting
confidence: 86%
“…Other researchers found that the compressive strength of concrete containing iron filings was higher than the plain concrete. Besides, the presence of iron filings enhances the ductility of concrete [17]. Kumar et al [18] investigated the effect of partial/total replacement of sand by iron ore tailing, as the fine aggregate on the compressive and flexural strength of reinforced concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Eine verallgemeinerbare Aussage zur thermischen Leit fähigkeit von Stahlfaserbeton lässt sich aus den vor liegenden Literaturergebnissen nur sehr schwer ableiten, da zum einen sehr unterschiedliche Betone (Normal beton NB, Selbstverdichtender Beton SVB, Ultrahoch fester Beton UHPC, Leichtbeton LB) sowie verschiedene Zementleime und ‐mörtel verwendet sowie zum anderen keine hohen Temperaturen betrachtet wurden. Im Allgemeinen wird jedoch deutlich, dass es kein einheitliches Prüfverfahren zur Bestimmung der thermischen Leitfähigkeit λ c von Betonen (mit und ohne Stahlfasern) gibt, eine deutliche Abhängigkeit des Ergebnisses vom verwendeten Prüfverfahren erkennbar ist; auch bei gleicher Zusammensetzung des Prüfbetons, sich die thermische Leitfähigkeit nicht proportional zum steigenden Stahlfasergehalt verändert, die Werte der thermischen Leitfähigkeit, ausgenommen in , über bzw. unter dem Grenzbereich der DIN EN 1992‐1‐2:2010 (ca.…”
Section: Literaturrechercheunclassified
“…Compared with molten salt, aluminate cement is much cheaper. The incorporation of functional materials into cementitious materials can effectively improve the thermal storage efficiency and mechanical behavior at high temperature [7][8][9][10]. What's more, cementitious/concrete material is an abundant and cheap resource, exhibiting non-toxicity and non-corrosiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Researches on functional materials such as steel fibers [11], nanomaterials [12,13], and phase change materials [14] in cementitious materials have been carried out extensively since the early 2000s. In the preparation of cementitious materials, there will be a portion of cement cannot be hydrated.…”
Section: Introductionmentioning
confidence: 99%